OC-012 Cytokine RNA profiles from Crohn's disease-derived, E coli-laden macrophages isolated by laser capture microdissection (1 cm). (23rd September 2015) - Rayment, N; Hudspith, B N; Elliott, T; Brostoff, J; Sanderson, J
Abstract : Introduction: Intestinal macrophages are important in the regulation of gut homeostasis. We and others have reported the persistence of strains of E coli in lamina propria macrophages in patients with Crohn's disease (CD). Studies of CD associated E coli show only low grade pathogenicity in keeping with hypothesis that there is a primary macrophage defect enabling bacterial persistence rather than a property of the E coli themselves. In a previous study we have successfully optimised the conditions necessary to extract RNA from laser dissected macrophages isolated from mucosal biopsies. This methodology has permitted the accurate identification and analysis of macrophages among a heterogeneous population of cells found within the lamina propria. Methods: Snap frozen mucosal biopsies were taken at routine colonoscopy from patients with CD (n=25) and controls (n=10) with normal mucosa. In addition, paired biopsy samples were taken from CD patients (n=6) from affected and unaffected areas. Using LCM combined with immuno-histochemistry (IHC), CD-68 positive macrophages containing clusters of E coli and those free of bacteria were identified, captured and total RNA extracted. qRT-PCR was then used to measure the expression of markers of macrophage activation (CD163, iNOS, COX-2) and cytokines (IL-1β, IL-6, IL-8, GM-CSF and TNF α). Results: A significant reduction in the expression of TNFα (p=0.001), IL-1b (p=0.01), IL-8 (p=0.004), GM-CSF (p=0.001), iNOS (p=0.001) and Cox-2 (p=0.0027) was seen when comparing CD macrophages laden with bacteria to unladen macrophages and controls. Expression of IL-6 was also reduced in laden macrophages but did not reach significance (p=0.49). Expression of CD163 was significantly increased in E coli laden macrophages (p=0.001) compared to unladen macrophages and controls. Laden and unladen macrophages isolated from affected and unaffected areas in the same patient had cytokine profiles which appeared to reflect the presence/absence of E coli and were therefore independent of inflammatory status. Conclusion: In patients with CD, we have shown altered expression of cytokines in E coli containing macrophages compared to those free of bacteria and to healthy controls. E coli persistence appears mainly to lead to reduced pro-inflammatory cytokine expression. The downstream effects of this in terms of chronic inflammation require further evaluation.